The work of waste: inside India's infra-economy - Gidwani, Vinay (Transactions - Institute of British Geographers (1965), 2015)
My essay1 focuses on the marginalised people whose livelihoods depend on gathering, sorting, transporting and selling garbage in India's huge informal economy, livelihoods now challenged as municipal governments contract the recycling of waste to corporations. The evolving, bumpy geography of the waste economy creates permanent border areas of primitive accumulation and both devalorised and valorised people and places. I make a case for understanding informal sector activities, such as the work of transforming the city's detritus, as part of a vast infraeconomy and the varied forms of labour performed within heterogeneous value chains of waste transformation as infrastructural labour that produces what Marx called capital's 'general' and 'external' conditions of production. Through close examination of the spatiotemporal lattice of informal municipal solid waste recycling, I demonstrate how these economies are at once highly organised and brittle, with each node in their value chains subject to disruption by state and market forces. While relative opacity, labour intensity of tasks and dependence on embodied knowledge (metis), indeed a 'bodily' feel for space, give informal economies the capacity to resist external efforts to transform, subsume or eradicate them; lack of social security and employment protections also means that workers and micro-enterprise owners within them inhabit the thin line between survival and failure, rendering them vulnerable to economic and political fluctuations. The upshot is that the labour of waste and other informal sector workers is critical for maintaining the quality of life desired by the well off in cities of the global South, but fails to get the recognition it deserves. Waste workers are poorly compensated, regularly stigmatised and frequently invisible in policy decisions. This is an enduring inequity that demands urgent correction.